Phosphoproteome reveals molecular mechanisms of aberrant rhythm in neurotransmitter‐mediated islet hormone secretion in diabetic mice. Issue 6 (27th June 2022) - He, Yunqiang; Fu, Qi; Sun, Min; Qian, Yu; Liang, Yucheng; Zhang, Jie; Gao, Rui; Jiang, Hemin; Dai, Hao; Liu, Yuwei; Xu, Xinyu; Chen, Heng; et al.
Abstract: Background: Acetylcholine (ACh) and norepinephrine (NE) are representative neurotransmitters of parasympathetic and sympathetic nerves, respectively, that antagonize each other to coregulate internal body functions. This also includes the control of different kinds of hormone secretion from pancreatic islets. However, the molecular mechanisms have not been fully elucidated, and whether innervation in islets is abnormal in diabetes mellitus also remains unclear. Methods and results: Immunofluorescence colocalization and islet perfusion were performed and the results demonstrated that ACh/NE and their receptors were highly expressed in islet and rapidly regulated different hormones secretion. Phosphorylation is considered an important posttranslational modification in islet innervation and it was identified by quantitative proteomic and phosphoproteomic analyses in this study. The phosphorylated islet proteins were found involved in many biological and pathological processes, such as synaptic signalling transduction, calcium channel opening and insulin signalling pathway. Then, the kinases were predicted by motif analysis and further screened and verified by kinase‐specific siRNAs in different islet cell lines (αTC1‐6, Min6 and TGP52). After functional verification, Ksr2 and Pkacb were considered the key kinases of ACh and NE in insulin secretion, and Cadps, Mlxipl and Pdcd4 were the substrates of these kinases measured by immunofluorescence co‐staining. Then, the decreased expression of receptors, kinases and substrates of ACh and NE were found in diabetic mice and the aberrant rhythm in insulin secretion could be improved by combined interventions on key receptors (M3 (pilocarpine) or α2a (guanfacine)) and kinases (Ksr2 or Pkacb). Conclusions: Abnormal innervation was closely associated with the degree of islet dysfunction in diabetic mice and the aberrant rhythm in insulin secretion could be ameliorated significantly after intervention with key receptors and kinases in the early stage of diabetes mellitus, which may provide a promising therapeutic strategy for diabetes mellitus in the future. Abstract : Rapid regulation of neurotransmitters in islet is exerted by altering proteins phosphorylation rather than expression levels. Proteins phosphorylation modulated by kinases play an important role in neurotransmitters ACh and NE mediated islet hormones secretion. Impaired innervation and aberrant rhythm of insulin secretion were found in islet of diabetic mice, which could be ameliorated after intervention with key receptors and kinases.